Badania marketingowe w europejskich instytucjach kształcenia ustawicznego - Światowy, Grażyna (Market Research in European Institutions of Long Life Learning, 2006)
The article talks over experiences of those education institutions in Europe, that has participated in realisation of "WIE - Weiterbildungsmarketing" project. The project was backed financially in years 2003-2005 with sources of SOKRATES-GRUNTVIG programme. It shows that building оf European society of knowledge and strong competition on the market are drivers increasing importance of marketing research. In practice of all project partners most important decisions and market analysis are focused on: creating an attractive educational offer; gain adequat (assuring economical profitability) number of clients - candidates for education; providing required education quality and appropriate client service (knowing and satisfaction their expectations, measuring satisfaction). Interesting example is a scenario and report from market research on attractiveness of the training offer "G3", created to be jointly launched on the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 300-308